NANORODS ZnO THIN FILM PERFORMANCE AS TRANSPARENT HEATERS. - L. Suhaim; A. H. Yuwono (Jurnal Sains Materi Indonesia, 2022)
NANORODS ZnO THIN FILM PERFORMANCE AS TRANSPARENT HEATERS. Transparent heaters have been used for various applications. In this research, a transparent heater made from ZnO nanorods has been successfully fabricated. ZnO nanorods were produced by using the chemical bath deposition method.The results of the XRD investigation showed that the ZnO_0.015 and ZnO_0.025 samples contained three and five ZnO peaks, respectively, with a hexagonal wurtzite crystal structure. The crystallite size increased along with the increase in the solution concentration from 71.198 nm to 82.924 nm. The morphological characterization of the samples using FE-SEM showed that ZnO_0.025 sample had a better surface covarege than ZnO_0.015 sample. The average diameters of ZnO_0.015 and ZnO_0.025 are 127.130 and 146.756 nm, respectively. The transmittance value decreased along with the increase of solution concentration which is from 55% to 53%. The value of the band gap energy decreased as the concentration of the seed solution increased from 3.25 eV to 3.20 eV. The resistivity values of ZnO_0.015 and ZnO_0.025 are 1.126 x 10-4 and 0.824 x 10-4Ωcm, respectively. From these results it appears that ZnO_0.025 sample has a more optimal performance as a transparent heater compared to ZnO_0.015 sample.